The relationship between fraud triangle and financial reporting fraud: the role of family ownership as moderating - Nilawati, Lia; Wijayanti, Provita (Proceeding International Conference on Accounting and Finance, 2024)
This research identifies the effect of the elements of the fraud triangle (financial targets, auditor changes, and effectiveness of supervision) which affect the occurrence of fraud on Financial Statement fraud with Family Ownership as a moderating variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The sample was selected using a purposive sampling technique and a final sample of 295 was obtained. The data used was secondary or quantitative data with an explanatory design and analyzed using the Partial Least Square (PLS) Structural Equation Modeling (SEM) method with the SmartPLS 3.2.9 operating system. The results of the study show that financial targets have a positive and significant effect on Financial Statement fraud, auditor changes do not have a significant effect on Financial Statement fraud, supervision effectiveness has a negative and significant effect on Financial Statement fraud. Family Ownership is only able to strengthen the influence of the effectiveness of supervision on Financial Statement fraud.